Inundation and erosion susceptibility in wave dominated beaches - Trindade,Jorge (2013)
Hydrodynamic forces over the beach sediments are the main driving factors affecting the frequency and magnitude of morphological changes in beach systems. Most of the time, these driving factors act in a foreseeable way and do not represent any danger either to the coastal systems or to their population. However, hydrodynamic forces are also capable of inducing high morphodynamic behaviour on the beach profiles and very often in a short period of time; this endangers people and property and leads to system retreat. The most common consequences of the occurrence of this type of phenomena over the landforms are costal inundation and erosion. Still, many coastal systems, especially beach systems, have recovery mechanisms. Resilience levels have a very important role in the beach morphodynamic status and exposure to potential damaging event assessments. The Portuguese West coast has a high wave energetic environment during winter, where waves with 5 year recurrence period can reach 9.2m and storms are frequent. This research aims to access beach hazard and susceptibility to inundation and erosion. Three beach systems were selected and monitored applying sequential profiling methodology over a four year period (2004-2007). Sta. Rita, Azul and Foz do Lizandro beaches are representative systems of the coastal stretch between Peniche and Cascais, which is a cliff dominated coast. Results from the monitoring campaigns are presented including volume budgets, beach face slope changes, berm occurrence and heights and planimetric coastline dynamics. A hazard and susceptibility assessment diagram and zonation are proposed, including the parameterization of local flood (i.e. mean sea level maximum spring tides, and surge and run-up levels) and erosion potentials (i.e. volume budget and beach planimetric dynamics).